No Effect of Digoxin on Rosuvastatin Pharmacokinetics in Healthy Subjects: Utility of Oita Combination for Clinical Drug–Drug Interaction Study. Issue 5 (4th June 2019) - Otani, Naoyuki; Wakuda, Hirokazu; Imai, Hiromitsu; Kuranari, Masae; Ishii, Yasuyuki; Ito, Yuko; Okubo, Akihiro; Ogawa, Osamu; Takeda, Kenji; Ohyama, Tetsuji; Hasunuma, Tomoko; Uemura, Naoto
Abstract : This study evaluated the utility of combination of digoxin (0.25 mg) and rosuvastatin (5 mg) as a new transporter (P‐glycoprotein/breast cancer resistance protein/organic anion‐transporting polypeptide (OATP)1B1/OATP1B3) probe cocktail (Oita combination) for drug–drug interaction (DDI) studies by demonstrating lack of DDI of digoxin on the pharmacokinetics (PKs) of rosuvastatin, as it was already known that rosuvastatin did not affect digoxin PK. This was an open‐label, two‐period study in which the primary end points were the geometric mean ratio (GMR) of the area under the plasma rosuvastatin concentration‐time curve from time zero to last (AUClast ) after rosuvastatin administration combined with digoxin to that after rosuvastatin administration alone and its 90% confidence interval (CI). As the GMR of AUClast was 0.974 and its 90% CI was 0.911–1.042, it was judged that digoxin does not affect rosuvastatin PK. Results of this study have rationalized utility of the Oita combination as a transporter probe cocktail for clinical DDI studies.